BRIAN B. SCHMIDT (ed.), Contextualizing Israel’s Sacred Writings: Ancient Literacy, Orality, and Literary Production. Ancient Israel and Its Literature 22. Atlanta, SBL Press, 2015, x + 374 pp. Paperback. ISBN 978–1–62837– 118–5. U$S 46,95 - Pfoh, Emanuel (2016)
Fil: Pfoh, Emanuel. Universidad Nacional de La Plata; Argentina